2005
DOI: 10.1158/1055-9965.epi-04-0913
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Consequences of Testing for Obesity Risk

Abstract: Objective: There is considerable hope that genetic susceptibility testing will motivate behavior that can prevent or reduce the risk of complex conditions such as obesity. This study examined potential behavioral consequences of such testing. Methods: Participants (n = 249) were randomly assigned to review one of four vignettes that asked them to imagine that they had been tested for their risk of becoming overweight or obese. The experimental factors were test type (genetic versus hormone test) and risk level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
6
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 23 publications
8
93
6
2
Order By: Relevance
“…22,23,31 Sanderson and Michie 21 found knowledge of high genetic risk of developing heart disease had a positive influence on intention to quit smoking. A study of genetic risk information for coronary heart disease by Wright et al 23 found the gene positive group had greater intentions to quit compared with the no test group.…”
Section: Outcomes Of Experimental Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23,31 Sanderson and Michie 21 found knowledge of high genetic risk of developing heart disease had a positive influence on intention to quit smoking. A study of genetic risk information for coronary heart disease by Wright et al 23 found the gene positive group had greater intentions to quit compared with the no test group.…”
Section: Outcomes Of Experimental Groupsmentioning
confidence: 99%
“…We utilized a common vignette paradigm that asks individuals to consider different hypothetical scenarios for genetic testing. [21][22][23] …”
Section: Introductionmentioning
confidence: 99%
“…When comparing genetic test results to other (nongenetic) biomarker results, those who were informed about an increased risk of becoming obese were found to have demonstrated higher intention to eat a healthy diet (Frosch et al 2005). The test type (genetic or hormone test) had no effect on the perceived risk or intention to eat a healthy diet.…”
Section: Discussionmentioning
confidence: 93%
“…The authors concluded that a positive obesity gene status would not adversely affect people's confidence in their ability to lose weight or control their eating behavior in difficult situations. Frosch et al (2005) published an analog study where 249 undergraduate students (BMI between 18.5 and 29.9) were asked about their attitudes, perceived behavior control and outcome expectancies towards eating a healthy diet after receiving a test result about a higher risk of becoming obese. Hypothetical test results were based either on a "genetic test" or on a "hormonal test" revealing increased or average risk of becoming obese.…”
Section: Obesitymentioning
confidence: 99%
“…82 There is also a risk that the group found to have a lower than average risk might unjustifiably feel that they are protected, and so be less motivated towards healthy behaviour. 56,83,84 So not everything that might result from new screening opportunities in this area is necessarily beneficial. However, the concept of individualised preventive medicine captures the imagination and is easy to sell.…”
Section: Screening For Genetic Sensitivity To Multifactorial Conditionsmentioning
confidence: 99%